2007
DOI: 10.1007/s10038-007-0154-1
|View full text |Cite
|
Sign up to set email alerts
|

Redefining the disease locus of 16q22.1-linked autosomal dominant cerebellar ataxia

Abstract: The 16q22

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 24 publications
0
32
0
Order By: Relevance
“…10,11,[14][15][16][17] Although the pathogenicity of the À16C4T substitution is controversial because of the discovery of two patients from families having 16q-ADCA, who did not have the À16C4T substitution, 10,11 it remains useful for the screening of 16q-ADCA in Japanese patients, as the À16C4T substitution has never been seen in Japanese controls thus far. 12 We found 32 pedigrees within 62 affected individuals who carried the À16C4T substitution of puratrophin-1. Nineteen patients were believed to be recessive for SCA or sporadic LCCA, but we revealed that all 19 had the haplotype block (SNP05-SNP06-À16C4T substitution of puratrophin-1), which is highly specific to 16q-ADCA.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…10,11,[14][15][16][17] Although the pathogenicity of the À16C4T substitution is controversial because of the discovery of two patients from families having 16q-ADCA, who did not have the À16C4T substitution, 10,11 it remains useful for the screening of 16q-ADCA in Japanese patients, as the À16C4T substitution has never been seen in Japanese controls thus far. 12 We found 32 pedigrees within 62 affected individuals who carried the À16C4T substitution of puratrophin-1. Nineteen patients were believed to be recessive for SCA or sporadic LCCA, but we revealed that all 19 had the haplotype block (SNP05-SNP06-À16C4T substitution of puratrophin-1), which is highly specific to 16q-ADCA.…”
Section: Discussionmentioning
confidence: 93%
“…We examined all the patients with puratrophin-1 alteration to determine whether they had a haplotype block (SNP05 and SNP06, highly specific to the 16q-ADCA allele), but neither of the SNPs was identified in 200 control chromosomes. 12 All patients had changes in SNP05 (G-A) and SNP06 (A-G), whereas none of the 96 controls had the haplotype block ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations